Concrete bridges affected by internal swelling reactions: Reactions mitigation and structural rehabilitation - Oliveira Santos Luís (MATEC Web of Conferences)
The increasing number of bridges affected by internal swelling reactions in concrete has raised significant concerns among bridge owners, given the serious consequences for their durability, serviceability and safety, which may involve high repair costs or even the replacement of severely damaged structures. This paper aims to provide an overview of the procedures used to prevent these reactions, with a particular emphasis on the methods used to mitigate their effects in affected bridges. Additionally, some examples of solutions applied to Portuguese bridges are presented.